Issues and problems in the implementation of management plans of protected areas under the national integrated protected area systems law the case of Mt. Kanlaon National Park. - Pechon, Romeo A Jr.; Tafgar, Aiken Rose M. (2002.)
This study examines the Mount Kanlaon Natural Park conservation experience and draws conclusions on the issues and problems pertaining to the implementation of management plans of protected areas under the National Integrated Protected Areas System (NIPAS) Law. The study finds that Mount Kanlaon Natural Park (MKNP) has well-formulated management plans but inadequate funding and lack of expertise and information have constrained the implementation of the said management plans. A host of nongovernmental organizations (HGOs) determined to help and provide livelihood to the migrants within the Mount Kanlaon Natural Park play a crucial role in shifting the migrants' alternatives with regard forest use. Moreover, NGOs' relative success is also hampered by bureaucratic strucures especially in completing all necessary requirements for the availment of funding for specific livelihood projects. Other state policies that contribute to the degeneration of forest resources need reforms, too. What is more, the role played by migrants within the MKNP is restricted; They are underrepresented in the planning and implementation of management policies designed to enhance biodiversity and forest protection. The study recommends stringent regulations in the declaration of protected areas in the future.
Research Paper (Undergraduate, Bachelor of Science in Economics-Management) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mt. Kanlaon National Park; Nastional Integrated Protected Area System Law -- Mt. Kanlaon Natural Park